2021
DOI: 10.3390/pathogens10060749
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Fasciola hepatica Excretory and Secretory Products Co-Immunoprecipitated Using Time Course Infection Sera

Abstract: Fasciola hepatica is a widespread pathogen that is known for its harmful effects on the health and productivity of ruminant animals. To identify the proteins present in all periods of infection with F. hepatica but not in those with Fasciola gigantica by shotgun liquid chromatography–tandem mass spectrometry (LC–MS/MS), we collected the ESPs and sera of F. hepatica and F. gigantica. In this study, the sheep were artificially infected with F. hepatica and the sera were collected at five different periods: 3 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Performance and characteristics of Fasciola ESAs fractionated by HAC The Fasciola ESAs are complex mixtures of antigens originated from adult ukes when maintained in vitro in a culture medium for a limited period (typically, 2-24 h 12,13,18,[26][27][28][29] ). Most Fasciola ESAs are secreted by the parasites into their blind-ending gut and then regurgitated through the oral suckle during an intermittent food in/waste out cycle 30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…Performance and characteristics of Fasciola ESAs fractionated by HAC The Fasciola ESAs are complex mixtures of antigens originated from adult ukes when maintained in vitro in a culture medium for a limited period (typically, 2-24 h 12,13,18,[26][27][28][29] ). Most Fasciola ESAs are secreted by the parasites into their blind-ending gut and then regurgitated through the oral suckle during an intermittent food in/waste out cycle 30,31 .…”
Section: Resultsmentioning
confidence: 99%
“…The early detection of F. hepatica infection based on circulating antigens has a higher application value in immunodiagnosis. To determine the early detection value of our established SA-ELISA in F. hepatica infection, we used the established SA-ELISA to detect circulating antigens in the serum of three sheep infected with F. hepatica on days 1, 3, 13, 21, 36, 89, 94, and 101, which were donated by Professor Chunren Wang of Heilongjiang Bayi Agricultural University in China [39]. We found that circulating antigens in the serums could be detected 13, 21, 36, and 89 days after infection, with the highest serum antigen level being observed at 36 days after infection (Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…Co-IP and MS are commonly used methods to detect protein–protein interactions in cells ( 11 , 12 ). We overexpressed the ERH gene and obtained 205 proteins that might directly or indirectly interact with ERH in human T24 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a series of analyses of ERH-binding proteins were carried out to explore the molecular biological mechanism of the ERH protein in tumorigenesis and BC development. Additionally, we overexpressed ERH protein in human T24 cells and then performed coimmunoprecipitation (co-IP) followed by shotgun mass spectrometry (MS), which is a high-throughput assay to characterize protein interactomes ( 11 ), to explore the proteins that interact with ERH in human T24 cells.…”
Section: Introductionmentioning
confidence: 99%